Donor Interventions and SME Networking in Industrial Clusters in Punjab Province, Pakistan - Anjum Fayyaz (Copenhagen Business School (CBS), 2017)
This PhD thesis is an outcome of the author's own reflections and efforts to come to terms with his experience working as the National Project Coordinator of the Industrial Cluster Development Program of an international donor agency in Pakistan, the IDA, for more than 8 years between 2001 and 2009. Thus, the author seeks to answer two interrelated questions in this thesis: a) How did the IDA interventions affect SME networks in the Lahore garments and Sialkot football clusters in Pakistan? b) Why did the IDA-supported SME networks in these clusters continue or discontinue after the IDA withdrew from both clusters? In this thesis, it is argued that a very limited number of empirical studies have addressed the subject of private sector development aid in industrial clusters in developing countries. In particular, very few studies aim at studying the sustainability of donor-financed interventions in industrial clusters in the Global South. Two articles in the thesis are dedicated to extending the very limited existing work on this topic. Both articles – the first on the Lahore garments cluster and the second on the Sialkot football manufacturing cluster in Pakistan – seek to analyze how the IDA's interventions affected the long-term sustainability of SME networks present in both clusters. In the case of the Lahore garments cluster, the IDA supported two networks in the cluster. One was known as the Lahore Garments Consortium and the other was named the Lahore Fashion Apparel Network. Both IDA financed networks initially seemed to flourish as they engaged in information sharing and joint action initiatives such as the joint procurement of raw materials for their production units. In the final analysis, it turned out however that the Lahore Garments Consortium continued to function long after the IDA had discontinued its support to the cluster whereas the Lahore Fashion Apparel Network was terminated after a very brief period in existence.
hdl:10398/9463
Keywords: 650